Etnografi Virtual Perilaku Impulsive Buying Remaja Muslimah Penggemar K-Pop di Surabaya - Khelsea, Yustika Okta; Tranggono, Didiek; Claretta, Dyva; Achmad, Zainal Abidin (Jurnal Komunikasi Islam, 2021)
This study examines the factors that influence teenager women Muslims (muslimah) of K-Pop fans' behavior in Surabaya regarding impulsive buying, the role of Twitter in eliciting their impulsive buying behavior, and to comprehend their understanding about the impact of impulsive buying as well. Using a virtual ethnographic approach, the findings have revealed that that impulsive buying behavior was influenced by friendship and the convenience facilities provided by Twitter related to information and promotions about K-Pop merchandise. This gave rise to a new culture of impulsive buying. However, teenager Muslim women of K-Pop fans are actually aware that impulsive buying behavior violates religious norms. Therefore, their behavior in purchasing K-Pop merchandise is based on rational choices.